2008
DOI: 10.2320/matertrans.e-mra2007890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Doping on Thermoelectric Properties of Arc-Melted and Hot-Pressed β-Rhombohedral Boron

Abstract: Thermoelectric properties of metal (V, Co, Zr, Sr, W)-doped -rhombohedral boron (-Boron) were examined in the temperature range from 353 K to 1073 K. Doping with V (V 1:5 B 105 ), which preferentially occupy the A 1 sites, results in a great increase of electrical conductivity and a negative Seebeck coefficient S, while doping Co, Zr, Sr or W (M 1:0 B 105 , M ¼ Co, Zr, Sr or W) also increases the though S remains positive. By crushing and hot pressing as-melted samples, the thermal conductivity was decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…However, TE modules require p-type and n-type materials with matching structure, and the lack of a suitable matching n-type counterpart for boron carbide has been a longstanding problem since icosahedral boron compounds have been found to be predominantly p-type. Slack first showed the n-type characteristics of vanadium-doped β -boron [11, 12], and extensive tests have been conducted for various dopants [1315]. However, all such n-type borides undergo metallization, whereby the Seebeck coefficient decreases with increasing temperature, in contrast to the temperature dependence of boron carbide.…”
Section: Introductionmentioning
confidence: 99%
“…However, TE modules require p-type and n-type materials with matching structure, and the lack of a suitable matching n-type counterpart for boron carbide has been a longstanding problem since icosahedral boron compounds have been found to be predominantly p-type. Slack first showed the n-type characteristics of vanadium-doped β -boron [11, 12], and extensive tests have been conducted for various dopants [1315]. However, all such n-type borides undergo metallization, whereby the Seebeck coefficient decreases with increasing temperature, in contrast to the temperature dependence of boron carbide.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the values of for these SPS samples are much lower than those for arc-melted bulk samples. 9) On the other hand, when x ! 1:5, increases with increasing V concentration owing to the formation of a second phase, VB 2 , which has a larger value of .…”
Section: Resultsmentioning
confidence: 99%
“…This is because a large increase in ' and a decrease in were possible owing to the metallic-covalent bonding conversion around the A 1 sites and to the decrease in grain size induced by SPS, respectively, although the value of S decreased and became negative. [9][10][11] As a result, V-doping is focused on in this paper. Table 1 shows the V concentration of three samples obtained by ICP analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies showed different results regarding dopant atom site preferences, however they are evidence of rather high solid solubility of such a large transition element in β-rh B. Contrasting data are available for the TE properties of Zrdoped β-rh B showing highly positive (for Zr 1.0 B 105 and Zr 0.8 B 105 [18,25]), and slightly negative (for Zr 1.0 B 105 [26]) values of Seebeck coefficient in the temperature ranges 200 K -300 K and 300 K -500 K respectively. In view of these inconsistencies and since the structure determination from powder diffraction data of ZrB~5 1 was only of a rather preliminary nature, in the current study we i) aimed to clarify the structure of metal rich Zrdoped β-rh B including the details of boron atom framework and dopant sites preferences as well as we ii) undertook the task to shed a light on the TE properties and their compositional dependence within the studied solubility range.…”
Section: Introductionmentioning
confidence: 87%